सामाजिक तथा सांस्कृतिक विभेदजन्य क्रियाकलापले अछाम क्षेत्रमा पारेको प्रभाव {Social and cultural discrimination activities Impact on the Acham region} (Voice of Teacher, 2022)
Division in society is mostly caused by differences in religious belie for practice, culture, behavior, and social activities. One of the main characteristics of any community is how they are each presented differently from one another. The split might be interpreted as social prejudice. Social discrimination occurs when a person, caste, race, or ethnic group is treated unfairly. It is a notion based on social and cultural constructs. It has existed throughout civilization since ancient times and continues to do so. It is constant and evolving idea. Discriminatory practices on the basis of social and cultural background have existed in Nepal since ancient times. It still permeates society today and has an effect on Achham's social and cultural sectors as well. Social and cultural prejudices were the central issues of this study, which also examined how it affected society. This research paper is analytical and descriptive in style. The qualitative data is the foundation of this study article. Depending on the situation, both primary and secondary sources of data were utilized in this work. Field surveys and interviews provided the primary data, while literature reviews provided the secondary data.